Focusing effects of ballistic transverse-quantized excitons in metal nanofilms - Makarov, Vladimir (2021)
New type of behavior of transverse-quantized excitons was discovered in metal nanofilms. These excitons demonstrated ballistic properties, propagating along nanofilms in straight lines along centimeter distances, reflecting at the film patch boundaries, and refracting at the boundary separating films of different materials but with the same exciton energy. Exciton reflection and focusing was explored in elliptically shaped metal film patches, along with exciton refraction on the boundary line separating two different film patches with compatible transverse-confinementgenerated electronic structures. These transverse-quantized excitons interact with phonons very weakly, prohibited by symmetry selection rules. The latter statement was confirmed in timeresolved experiments. Weak interactions explain rectilinear trajectories and long lifetimes of excitons in thin metal films.